Supercritical carbon dioxide debinding in metal injection molding (MIM) process - Kim, YH; Lee, YW; Park, JK; Lee, CH; Lim, JS (KOREAN INST CHEM ENGINEERS, 2002)
The conventional debinding process in metal injection molding (MIM) is critical, environmentally unfriendly and time consuming. On the other hand, supercritical debinding is thought to be an effective method appropriate for eliminating the aforementioned inconvenience in the prior art. In this paper, supercritical debinding is compared with the conventional wicking debinding process. The binder removal rates in supercritical CO, have been measured at 333.15 K, 348.15 K, and 358.15 K in the pressure range from 20 MPa to 28 MPa. After sintering, the surface of the silver bodies were observed by using SEM. When the supercritical CO, debinding was carried out at 348.15 K, all the paraffin wax (71 wt% of binder mixture) was removed in 2 hours under 28 MPa and in 2.5 hours under 25 MPa. We also studied the cosolvent effects on the binder removal rate in the supercritical CO2 debinding. It was found that the addition of non-polar cosolvent (n-hexane) dramatically improves the binder removal rate (more than 2 times) for the paraffin wax-based binder system.
Keywords: SOLUBILITY; COSOLVENTS; CERAMICS; BEHAVIOR; POLAR